Short-wave IR ultrafast fiber laser systems : current challenges and prospective applications - Kirsch, D. C. (2021)
Ultrashort pulse generation at the short-wave infrared (SWIR) wavelength ranges from 1.6 to 2.5μm and together with benefits of the all-fiber design has transformed lasers into an essential tool for industrial, technological, scientific, environmental, and medical applications. With the development of pumping sources and fiber components, ultrafast SWIR fiber lasers have drawn exceptional research and industrial attention over the last decade, resulting in the achievement of comparable performance or even surpassing well-established near-IR sources. Exceptionally compact, highly stable, cost-effective, and maintenance-free ultrafast fiber lasers operating at the SWIR range are currently well on the way to be commercially employed. This invited Perspective article gives a comprehensive overview of the most significant achievements enabling ultrafast generation at SWIR, including up-to-date gain fibers and saturable absorbers, nonlinear process, and laser architectures. This article highlights the perspectives and strategies for further maturing of the field of SWIR fiber lasers and pathways for the improvement of the performance, overcoming existing bottlenecks and challenges toward reducing pulse durations, tunability of repetition rate, and power upscaling. The advancement of the ultrafast SWIR laser development is projected until the landscape of existing technologies, driven by these ultimate sources, and potential applications, emerging on the horizon.